Structural analysis of Castanea sativa Mill. leaves from different regions in the tree top - Pinto,Teresa Maria (2011)
The aim of this work was to perform the histological characterization of the C. sativa leaves of three Portuguese cultivars to establish comparison among the leaves of the different quadrants in accord and with the cardinal points of the tree top and among different cultivars of this species, using light microscopy (OM) and scanning electron microscopy (SEM). Measurements were also carried out for the leaf tissue thickness, stomatal density, leaf area in the four tree top quadrants. The leaves turned to the North had lesser thickness of mesophyll mainly due to lower amount of palisade parenchyma. The stomatal density was significantly lower in these leaves, unlike the leaf area that has the highest expression.